Effect of Repetitive Glucose Spike and Hypoglycaemia on Atherosclerosis and Death Rate in Apo E-Deficient Mice - Kenichi Nakajima; Tomoya Mita; Yusuke Osonoi; Kosuke Azuma; Toshiyuki Takasu; Yoshio Fujitani; Hirotaka Watada (International Journal of Endocrinology)
Epidemiological data suggest that postprandial hyperglycaemia and hypoglycaemia are potential risk factors for cardiovascular disease. However, the effects of repetitive postprandial glucose spikes, repetitive hypoglycaemia, and their combination on the progression of atherosclerosis remain largely unknown. The present study investigated the effects of rapid rises and falls in glucose, and their combination, on the progression of atherosclerosis in apolipoprotein (apo) E-deficient mice. In this study, apo E-deficient mice with forced oral administration of glucose twice daily for 15 weeks were used as a model of repetitive postprandial glucose spikes, and apo E-deficient mice given an intraperitoneal injection of insulin once a week for 15 weeks were used as a model of repetitive hypoglycaemia. In addition, we established a model of both repetitive postprandial glucose spikes and hypoglycaemia by combining the above interventions. Atherosclerosis was evaluated in all mice by oil red O staining. Administration of ipragliflozin, a selective inhibitor of sodium-glucose cotransporter 2, in the mouse model of repetitive glucose spikes inhibited the progression of atherosclerosis, whereas long-term repetitive glucose spikes, repetitive hypoglycaemia, and their combination had no significant impact on atherosclerosis. However, repetitive hypoglycaemia was associated with poor survival rate. The results showed that repetitive hypoglycaemia reduces the survival rate without associated progression of atherosclerosis in apo E-deficient mice.